The major cysteine proteinase (cruzipain) from Trypanosoma cruzi is antigenic in human infections. - Martinez, J (1991)
Antibodies against the major cysteine proteinase (cruzipain) from Trypanosoma cruzi were detected in human sera obtained from patients with chronic Chagas' disease. Not only the intact 60-kDa enzyme but also its 25-kDa self-proteolysis fragment are antigenic in vivo. Although T. cruzi antigens 13 and 36 also reacted with the apparently monospecific antiproteinase serum, the antigenicity of cruzipain to human patients is genuine, since its reactivity was not modified by the adsorption of human sera with the recombinant proteins 13 and 36.